A method for preparing a friction-reducing and wear-resistant coating for GH4169 material
By performing metal ion implantation and chromium oxide thin film deposition on the surface of GH4169 material and performing non-metal ion implantation, the problem of GH4169 material being easily worn and failed under extreme operating conditions is solved, significantly improving the wear resistance and bonding of the coating, and extending the service life of the parts.
Patent Information
- Application Number
- CN202510058349.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-08
AI Technical Summary
GH4169 material has a high friction coefficient under extreme operating conditions such as high temperature, ultra-low temperature, high speed, heavy load, etc., which is prone to wear and failure, resulting in a shortening of the service life of the parts.
The surface of GH4169 material was implanted with MEVVA ion source to form an ion implantation transition interface layer, and then the chromium oxide film was deposited by magnetron sputtering method, and non-metal ion implantation was performed on the coating surface to enhance the binding force and wear resistance of the coating.
It significantly improves the friction and wear resistance properties of the chromium oxide friction-reducing wear-resistant coating and its binding force with the substrate, extends the service life of GH4169 material parts, and reduces the risk of coating peeling.
Smart Images

Figure CN119776763A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface treatment of metal materials, and in particular to a method for preparing a friction-reducing and wear-resistant coating for GH4169 material. Background Art
[0002] GH4169 material (Inconel 718) is a nickel-based high-temperature alloy with excellent mechanical properties, good corrosion resistance and processing performance. It is one of the commonly used metal materials in aerospace and is often used in key components of aircraft and rocket engines. With the continuous development of aviation and aerospace technology, higher requirements are also placed on the performance of components used under special working conditions. However, under extreme working conditions such as high temperature, ultra-low temperature, high speed, and heavy load, GH4169 alloy has a high friction coefficient and is prone to wear and failure, which seriously affects the service life of components. Therefore, wear-resistant treatment of GH4169 material is required to improve the service life of components.
[0003] At present, thermal spraying technology is commonly used in China to prepare chromium oxide wear-resistant coating on the surface of parts to improve the wear resistance of GH4169 material parts. However, thermal spraying technology has some disadvantages. Its hard wear-resistant coating is thicker and has a larger surface roughness. The surface still needs secondary processing, and the yield rate is low. In addition, the coating has the risk of peeling off under ultra-low temperature conditions. The peeled hard coating particles will not only cause abrasive wear of the workpiece and accelerate its failure, but also flow into the interior of the parts, causing fatal risks.
[0004] Therefore, how to achieve controllable coating design and prepare high-quality chromium oxide anti-friction and wear-resistant coating is an urgent problem to be solved. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a friction-reducing and wear-resistant coating for GH4169 material, which can improve the friction and wear resistance of the friction-reducing and wear-resistant coating and the bonding force between the friction-reducing and wear-resistant coating and the substrate, thereby improving the friction and wear resistance of GH4169 material parts, extending the service life, and solving the problem of easy wear and failure of GH4169 material parts.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] A method for preparing a friction-reducing and wear-resistant coating for GH4169 material comprises the following steps:
[0008] S100, surface polishing and chemical ultrasonic cleaning of GH4169 material;
[0009] S200, using a MEVVA ion source to perform metal ion implantation on the surface of the GH4169 material, wherein the implanted metal ions are one of chromium ions or nickel ions, to form an ion implantation transition interface layer;
[0010] S300, depositing a chromium oxide film on the surface of the ion implantation transition interface layer by a magnetron sputtering method to obtain a chromium oxide friction-reducing and wear-resistant coating;
[0011] S400, using a gas ion source or a MEVVA ion source to perform non-metallic ion implantation on the chromium oxide anti-friction and wear-resistant coating to form a reinforced anti-friction and wear-resistant coating.
[0012] Specifically, the step S100 includes:
[0013] S101, polishing the surface of the GH4169 material with a sander;
[0014] S102, first use a metal degreasing solvent to remove grease on the surface of the GH4169 material, soak it in tetrachloroethylene for 15-30 minutes, and ultrasonically clean it; then use a metal rust remover to clean the rust spots on the surface of the GH4169 material, soak it in acetone for 15-30 minutes, and ultrasonically clean it; finally, soak the GH4169 material in alcohol for 15-30 minutes, and ultrasonically clean it; wipe it dry with a clean silk cloth, place it in a vacuum oven, set the temperature of the vacuum oven to 50-70°C, and take it out after 2-4 hours.
[0015] Specifically, during the metal ion implantation process of step S200, the suppression voltage is 0.1-10 kV, the suppression current is 1-15 mA, the extraction voltage is 30-100 kV, and the extraction current is 1-20 mA.
[0016] Specifically, in step S200, the metal source used for metal ion implantation is a metal chromium target or a nickel target with a purity of more than 99.9%, and the total ion implantation dose is 2 to 8×10 17 ions / cm 2 .
[0017] Specifically, in step S300, argon gas with a purity of 99.99% is introduced into the vacuum chamber, and the argon gas flow rate is 10 to 50 sccm, and magnetron sputtering is performed using a chromium oxide target with a purity of more than 99.9%.
[0018] Specifically, in step S300, the sputtering voltage of the magnetron sputtering process is 300-800V, the sputtering current is 0.1-5A, the sputtering gas pressure is 0.01-0.1Pa, and the sputtering time is 1-10min.
[0019] Optionally, in step S400, a gas ion source is used to perform non-metallic ion implantation on the workpiece to be processed of GH4169 material, the non-metallic ions implanted are nitrogen ions, and the gas source used for the non-metallic ion implantation is high-purity nitrogen with a purity of more than 99.99%; the process of performing non-metallic ion implantation on the workpiece to be processed of GH4169 material using a gas ion source includes:
[0020] The GH4169 material was placed in the vacuum chamber of the ion implantation equipment and fixed on the fixture. The vacuum was evacuated to a vacuum degree of 1-3×10 -3 Pa, high-purity nitrogen is introduced into the vacuum chamber to maintain the pressure at 1~5×10 -3 pa; turn on the filament power supply and grid voltage, adjust the acceleration voltage to 50-100 kV, the acceleration current to 1-10 mA, the suppression voltage to 0.5-5 kV, the suppression current to 0-10 mA, and control the total ion implantation dose to 1-6 × 10 17 ions / cm 2 .
[0021] Optionally, a MEVVA ion source is used to perform non-metallic ion implantation on a workpiece made of GH4169 material to be processed, wherein the implanted non-metallic ions are carbon ions, and the non-metallic ion target material used is a carbon target with a purity greater than or equal to 99.9%; the process of using the MEVVA ion source to perform non-metallic ion implantation on a workpiece made of GH4169 material to be processed comprises: adjusting the arc current to 1-10A, adjusting the acceleration voltage to 10-100kV, the implantation energy of each carbon ion implantation is 10keV to 200keV, preferably 10keV to 100keV, and controlling the total ion implantation dose to be 1 to 6×10 17 ions / cm 2 .
[0022] Beneficial effects achieved by the technical solution of the present invention:
[0023] The method for preparing the friction-reducing and wear-resistant coating for GH4169 material of the present invention performs non-metallic ion implantation treatment and metal ion implantation treatment on the substrate and the friction-reducing and wear-resistant coating respectively before and after depositing the chromium oxide friction-reducing and wear-resistant coating, which can effectively improve the bonding force between the friction-reducing and wear-resistant coating and the substrate, improve the wear resistance of the friction-reducing and wear-resistant coating, reduce the risk of peeling of the friction-reducing and wear-resistant coating, solve the problem of easy wear and failure of GH4169 material parts and components, and extend the service life of GH4169 material parts and components. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a test result diagram of the friction coefficient of GH4169 material without anti-friction and wear-resistant coating;
[0025] Figure 2This is a graph showing the test results of the friction coefficient of the GH4169 material in Example 2 after the anti-friction and wear-resistant coating is prepared. DETAILED DESCRIPTION
[0026] In order to better explain the present invention, the present invention is described in detail with reference to the embodiments of the present invention, and the main contents of the present invention are further illustrated in conjunction with specific examples, but the content of the present invention is not limited to the following examples. If no specific technology or conditions are indicated in the examples, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents or instruments is not indicated, they are all conventional products that can be obtained commercially.
[0027] The present invention is further described in detail below through examples and related performance tests.
[0028] Example 1 Preparation of anti-friction and wear-resistant coating on the surface of GH4169 material
[0029] Step S100, polish the surface of the GH4169 material with a sander; soak the polished GH4169 material in tetrachloroethylene for 5-15 minutes, and ultrasonically clean it; soak it in acetone for 5-15 minutes, and ultrasonically clean it; finally soak the GH4169 material in alcohol for 5-15 minutes, and ultrasonically clean it. Dry it with a clean silk cloth, dry it in a vacuum oven for 1-2 hours, and then take it out.
[0030] Step S200, using MEVVA ion source to perform metal nickel ion implantation on the surface of GH4169 material to form an ion implantation transition interface layer; this step uses a metal nickel target material with a purity of more than 99.9%. During the ion implantation process, the suppression voltage is 6KV, the suppression current is 6mA, the extraction voltage is 40kV, and the extraction current is 2mA; the total ion implantation dose is 4×10 17 ions / cm 2 .
[0031] Step S300, preparing a chromium oxide anti-friction and wear-resistant coating by magnetron sputtering, specifically: introducing argon gas with a purity of 99.99% into the vacuum chamber, using a chromium oxide target with a purity of more than 99.9% for magnetron sputtering, adjusting the sputtering voltage to 500V, the sputtering current to 3A, the sputtering pressure to 0.05Pa, the sputtering time to 3min, and the argon gas flow rate to 30sccm, to prepare a chromium oxide anti-friction and wear-resistant coating on the metal transition layer.
[0032] Step S400, non-metallic nitrogen ion implantation is performed on the chromium oxide friction-reducing and wear-resistant coating using a gas ion source, specifically, the GH4169 material after the chromium oxide friction-reducing and wear-resistant coating is placed in a fixture in the vacuum chamber of the ion implantation equipment for fixation, and the vacuum is evacuated to a vacuum degree of 1 to 3×10 -3Pa, high-purity gas is introduced into the vacuum chamber. The gas source is 99.99% pure nitrogen. The gas flow rate is controlled and the gas pressure is maintained at 1-5×10 -3 pa; turn on the filament power supply and grid voltage, adjust the acceleration voltage to 50 kV, the acceleration current to 6 mA, the suppression voltage to 3 kV, and the suppression current to 5 mA; control the total ion implantation dose to 1.5 × 10 17 ions / cm 2 .
[0033] Example 2 Preparation of anti-friction and wear-resistant coating on the surface of GH4169 material
[0034] Step S100, polishing the surface of the GH4169 material with a sander; then soaking the polished GH4169 material in tetrachloroethylene for 5-15 minutes, ultrasonic cleaning; soaking it in acetone for 5-15 minutes, ultrasonic cleaning; finally soaking the GH4169 material in alcohol for 5-15 minutes, ultrasonic cleaning; wiping it dry with a clean silk cloth, placing it in a vacuum oven to dry and then taking it out.
[0035] Step S200, using a MEVVA ion source to perform metal chromium ion implantation on the surface of the GH4169 material to form an ion implantation transition interface layer; this step uses a metal chromium target with a purity of more than 99.9%. During the ion implantation process, the suppression voltage is 8KV, the suppression current is 12mA, the extraction voltage is 50kV, the extraction current is 5mA, and the total ion implantation dose is controlled to be 6×10 17 ions / cm 2 .
[0036] Step S300, preparing a chromium oxide anti-friction and wear-resistant coating by magnetron sputtering, specifically: introducing argon gas with a purity of 99.99% into the vacuum chamber, using a chromium oxide target with a purity of more than 99.9% for magnetron sputtering, adjusting the sputtering voltage to 700V, the sputtering current to 5A, the sputtering pressure to 0.1Pa, the sputtering time to 5min, and the argon gas flow rate to 50sccm, to prepare a chromium oxide anti-friction and wear-resistant coating on the metal transition layer.
[0037] Step S400, non-metallic carbon ion implantation is performed on the chromium oxide friction-reducing and wear-resistant coating using a MEVVA ion source. This step uses a carbon target with a purity of 99.9%. During the ion implantation process, the arc current is 8A, the acceleration voltage is 65kV, the injection energy of each carbon implantation is 65keV, and the total ion implantation dose is 3×10 17 ions / cm 2 .
[0038] <Performance Test>
[0039] 1. Surface friction and wear test
[0040] Surface friction and wear tests were performed on the GH4169 material (substrate) without the anti-friction and wear-resistant coating and the GH4169 material after the anti-friction and wear-resistant coating was prepared in Example 1-2.
[0041] The friction and wear tester was used, the grinding ball was silicon nitride ball, the load was 50g, the friction radius was 4mm, and the test time was 30min. The experiment was repeated 3 times and the average value was taken.
[0042] The wear volume was measured using a surface profiler and the wear rate was calculated. The experiment was repeated three times for each sample and the average value was taken.
[0043] The surface friction and wear test results are as follows:
[0044] Base material: friction coefficient 0.7, wear rate 8.7×10 –6 mm 3 / (N·m).
[0045] Example 1: Friction coefficient 0.32, wear rate 4.5×10 –6 mm 3 / (N·m).
[0046] Example 2: Friction coefficient 0.13, wear rate 1.9×10 –6 mm 3 / (N·m).
[0047] Figure 1 This is the test result of the friction coefficient of GH4169 material (substrate). Figure 2 The friction coefficient test result of the GH4169 material of Example 2 after preparing the anti-friction and wear-resistant coating is shown in the figure. After preparing the anti-friction and wear-resistant coating, the wear resistance of the GH4169 material of Example 1 is improved by more than 2 times. After preparing the anti-friction and wear-resistant coating, the wear resistance of the GH4169 material of Example 2 is improved by more than 5 times.
[0048] 2. Coating scratch test
[0049] The layer-base bonding strength of the friction-reducing and wear-resistant coatings prepared in Example 1-2 was tested using a nano scratch tester, and each sample was tested three times to obtain an average value.
[0050] The test result of the layer-base bonding strength of Example 1 is 29 N. The test result of the layer-base bonding strength of Example 2 is 43 N.
[0051] The above results show that the method for preparing the friction-reducing and wear-resistant coating for GH4169 material of the present invention can effectively improve the wear resistance of the friction-reducing and wear-resistant coating and the bonding force between the friction-reducing and wear-resistant coating and the substrate.
Claims
1. A method for preparing a friction-reducing and wear-resistant coating for GH4169 material, characterized in that: The steps include: S100, surface polishing and chemical ultrasonic cleaning of GH4169 material; S200, using a MEVVA ion source to perform metal ion implantation on the surface of the GH4169 material, wherein the implanted metal ions are chromium ions or nickel ions, to form an ion implantation transition interface layer; S300, depositing a chromium oxide film on the surface of the ion implantation transition interface layer by a magnetron sputtering method to obtain a chromium oxide friction-reducing and wear-resistant coating; S400, using a gas ion source or a MEVVA ion source to perform non-metallic ion implantation on the chromium oxide anti-friction and wear-resistant coating to form a reinforced anti-friction and wear-resistant coating.
2. The method for preparing the friction-reducing and wear-resistant coating for GH4169 material according to claim 1, characterized in that: The step S100 specifically includes: S101, polishing the surface of the GH4169 material with a sander; S102, first use a metal degreasing solvent to remove grease on the surface of the GH4169 material, soak it in tetrachloroethylene for 15-30 minutes, and ultrasonically clean it; then use a metal rust remover to clean the rust spots on the surface of the GH4169 material, soak it in acetone for 15-30 minutes, and ultrasonically clean it; finally, soak the GH4169 material in alcohol for 15-30 minutes, and ultrasonically clean it; wipe it dry with a clean silk cloth, place it in a vacuum oven, set the temperature of the vacuum oven to 50-70°C, and take it out after 2-4 hours.
3. The method for preparing the friction-reducing and wear-resistant coating for GH4169 material according to claim 1, characterized in that: In the step S200, the suppression voltage of the metal ion implantation process is 0.1-10 kV, the suppression current is 1-15 mA, the extraction voltage is 30-100 kV, and the extraction current is 1-20 mA.
4. The method for preparing the friction-reducing and wear-resistant coating for GH4169 material according to claim 1, characterized in that: In step S200, the metal source used for metal ion implantation is a metal chromium target or a nickel target with a purity of more than 99.9%, and the total ion implantation dose is 2 to 8×10 17 ions / cm 2 .
5. The method for preparing the friction-reducing and wear-resistant coating for GH4169 material according to claim 1, characterized in that: In the step S300, argon gas with a purity of 99.99% is introduced into the vacuum chamber, and the argon gas flow rate is 10-50 sccm, and magnetron sputtering is performed using a chromium oxide target with a purity of more than 99.9%.
6. The method for preparing the friction-reducing and wear-resistant coating for GH4169 material according to claim 1, characterized in that: In the step S300, the sputtering voltage of the magnetron sputtering process is 300-800V, the sputtering current is 0.1-5A, the sputtering gas pressure is 0.01-0.1Pa, and the sputtering time is 1-10min.
7. The method for preparing the friction-reducing and wear-resistant coating for GH4169 material according to claim 1, characterized in that: In the step S400, a gas ion source is used to perform non-metallic ion implantation on the GH4169 material. The non-metallic ions implanted are nitrogen ions. The gas source used for the non-metallic ion implantation is high-purity nitrogen with a purity of more than 99.99%.
8. The method for preparing the friction-reducing and wear-resistant coating for GH4169 material according to claim 7, characterized in that: In step S400, the non-metallic ion implantation process includes: placing the GH4169 material in a vacuum chamber of an ion implantation device and fixing it on a fixture, evacuating the chamber to a vacuum degree of 1 to 3×10 -3 Pa, high-purity nitrogen is introduced into the vacuum chamber to maintain the pressure at 1~5×10 -3 pa; turn on the filament power supply and grid voltage, adjust the acceleration voltage to 50-100 kV, the acceleration current to 1-10 mA, the suppression voltage to 0.5-5 kV, the suppression current to 0-10 mA, and control the total ion implantation dose to 1-6 × 10 17 ions / cm 2 .
9. The method for preparing the friction-reducing and wear-resistant coating for GH4169 material according to claim 1, characterized in that: In the step S400, a MEVVA ion source is used to perform non-metallic ion implantation on the GH4169 material. The implanted non-metallic ions are carbon ions. The target material used for the non-metallic ion implantation is a carbon target with a purity greater than or equal to 99.9%.
10. The method for preparing the friction-reducing and wear-resistant coating for GH4169 material according to claim 9, characterized in that: In step S400, the process of non-metallic ion implantation includes: adjusting the arc current to 1-10A, adjusting the acceleration voltage to 10-100kV, the injection energy of each carbon ion injection is 10keV-200keV, and controlling the total ion implantation dose to 1-6×10 17 ions / cm 2 .